THE PLACE AND ROLE OF REHABILITATION IN PREVENTING DRUG ADDICTION - Kholova Mohigul Shavkatovna, Kurbanova Sabina Ziyodulla daughter (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
his in the article addiction social problem as analysis deviant behavior shape as seeing Drug addiction to society, especially young generation to the mind negative impact deep analysis Also, in the article addiction prevent in receiving rehabilitation process place and importance separately accent with Rehabilitation in the process psychological, social and pedagogical approaches integration through healthy marriage in style return opportunities analysis The approach innovative and modern forms based on efficiency increase roads showing is given.